Robust loop shaping-fuzzy gain scheduling control of a servo-pneumatic system using particle swarm optimization approach - Kaitwanidvilai, Somyot; Olranthichachat, Piyapong (My University, 2011)
In this paper, a new technique called robust loop shaping-fuzzy gain scheduled control (RLS-FGS) is proposed to design an effective nonlinear controller for a long stroke pneumatic servo system. In our technique, a nonlinear dynamic model of a long stroke pneumatic servo plant is identified by the fuzzy identification method and is used as the plant for our design. The structure of local controllers is selected as PID control which is proven by many research works that this type of control has many advantages such as simple structure, well understanding, and high performance. The proposed technique uses particle swarm optimization (PSO) to find the optimal local controllers which maximize the average stability margin. In addition, performance weighting function which is normally difficult to obtain is automatically determined by PSO. By the proposed technique, the RLS-FGS controller can be designed, and the structure of local controllers is still not complicated. As seen in the simulation and experimental results, our proposed technique is better than the classical gain scheduled PID controller tuned by pole placement and the conventional fuzzy PID controller tuned by ISE method in terms of robust performance. © 2010 Elsevier Ltd. All rights reserved.
Keywords: Fixed-structure robust control; Fuzzy gain scheduling control; Particle swarm optimization; Robust loop shaping control